Improving Students’ Reading Comprehension Using Project-Based Learning at VIII F Grade of SMPN 43 Surabaya - Sajad Wiratmo; Bekti Wirawati; Erna Sulistyawati (Edumaspul: Jurnal Pendidikan, 2022)
The objective of this study to describe whether the Project-based learning method can improve students’ reading comprehension at VIII F grade of SMPN 43 Surabaya. The research design uses the Classroom Action Research (CAR) method. The time was arranged from May to September 2022. There were 39 students in the class. The class consisted 20 boys and 19 girls. The student’s score indicated the result of implementation. The students’ score increase. The Project-based learning method improved the students’ achievement in reading notice text significantly and helped the students become active and creative in learning. The Planning, Acting, Observing, and Reflecting of teaching-learning use of Project-based learning were successfully conducted. It can be shown that researchers can make a lesson plan and apply PJBL as a method in teaching reading Notice text. The teacher can combine Project-based learning with another method if conditionally to make students don’t bored while receiving the materials.